1995
DOI: 10.37570/bgsd-1995-42-08
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cenozoic sequences in the southeastern North Sea Basin

Abstract: The Upper Cenozoic deposits, which cover the "mid-Miocene unconformity" in the southeastern North Sea Basin are subdivided into thirty-one sequences. Progradation from the east to the west is observed. The lowstand systems tracts appear seismically as prograding wedges. The top lowstand surface is recognized as a toplap surface in areas where high-angle progradation dominates the stratal pattern, indicating the presence of a bypass zone formed during lowstand progradation. The maximum flooding surface is ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Different incision mechanisms have been described for TVs, and there has long been a debate about whether the incision could be explained with fluvial erosion (Donovan, 1972;Salomonsen, 1995;Sørensen and Michelsen, 1995) or whether pressurized subglacial erosion is the more likely mechanism (Jentzsch, 1884;Kuster and Meyer, 1979;Piotrowski, 1994). Our high-resolution longitudinal profiles along a single-incision TV show that the incision has overcome significant morphological highs of over 75 m over a 500 m distance, which is a significant gradient when compared to earlier studies by Stewart et al (2013), who showed a maximum gradient of approx.…”
Section: Discussionmentioning
confidence: 99%
“…Different incision mechanisms have been described for TVs, and there has long been a debate about whether the incision could be explained with fluvial erosion (Donovan, 1972;Salomonsen, 1995;Sørensen and Michelsen, 1995) or whether pressurized subglacial erosion is the more likely mechanism (Jentzsch, 1884;Kuster and Meyer, 1979;Piotrowski, 1994). Our high-resolution longitudinal profiles along a single-incision TV show that the incision has overcome significant morphological highs of over 75 m over a 500 m distance, which is a significant gradient when compared to earlier studies by Stewart et al (2013), who showed a maximum gradient of approx.…”
Section: Discussionmentioning
confidence: 99%